Clinical implications of novel diagnostic and surgical methods in the intraocular surgery of pediatric and adult patients - Lytvynchuk, Lyubomyr; Justus Liebig University Giessen (My University, 2021)
Progress and improvement of the novel surgical approaches for intraocular surgery has advanced the field significantly. In this thesis, innovations are presented in the three area, which are of considerable importance to intraocular surgery: (1) new intraoperative diagnostics, (2) new surgical techniques, and (3) new surgical instruments. 1. New diagnostic techniques Inventions of the intraoperative optical coherent tomography and its application into the clinical practice have modernized the field of the ocular surgery (Binder et al. 2011). The first review of the commercially available iOCT systems and its feasibility for eye surgery was recently reported in a book chapter (Lytvynchuk et al. 2017). In this review the authors summarized the current information about technical characteristics of the iOCT systems, principles of intraoperative imaging, ways of data post-processing, as well as data regarding its application for anterior and posterior eye segments with presentation of clinical cases. It was demonstrated that the use of iOCT imaging enabled to investigate in real-time the pathophysiology of different eye disorders, revealing numerous intra-surgical findings, which have extended our understanding of the course of these diseases and the influence of the surgical procedure on the clinical outcomes. In a second study, we applied the iOCT approach to investigate the real position of the intraocular lenses inside the capsular bag at the end of the standard lens-in-the-bag surgery (Lytvynchuk et al. 2016). This issue is significantly associated with the development of postoperative capsular opacification. For the first time, we were able to show that at the end of the surgery the contact between posterior lens capsule and IOL optic is a rare event (12.9%). This represents a new aspect to explain the residual rate of the PCO in spite of the use of square edge IOL with “no space – no cells” concept. These findings demonstrate that the absence of the contact between IOL and posterior capsule in the vast majority of cases results in postoperative proliferation and migration of the lens epithelial cells into the retrolental optical zone. Within this thesis, the iOCT method was also applied during surgeries of the most sensitive area of the retina, the fovea centralis, with a particular emphasis on tissue reactions following surgical treatment of macular holes (Lytvynchuk et al. 2019). The inverted internal limiting membrane flap technique is a novel and very challenging approach to treat macular holes of different origin. In our study we applied iOCT during macular hole surgery with IILMFT to evaluate the possibilities and consequences of the new approach. The study results demonstrated the advantages of the new technique in comparison to convectional ILM peeling. We documented for the first time that IILMFT avoided the intraoperative iatrogenic enlargement of the macular hole size and even more, allowed to minimize the basal size of it. Additionally, the use of iOCT enabled to reassure the proper position of the inverted ILM flap at the very end of the surgery after air tamponade was done and visual control was impossible. Every step of the novel surgery could be visualized and was therefore well controlled, which improves the safety of such an approach. Modern vitreoretinal surgeries for the treatment of degenerative retinal diseases might become an important field of application of iOCT. One of our studies was focused on the feasibility of iOCT imaging during Argus II retinal prosthesis implantation in patients with retinitis pigmentosa (Binder and Lytvynchuk 2016). The study results demonstrated that iOCT assisted surgery enabled the detection of residual epiretinal membranes in the macular area. These membranes need to be removed before Argus II implantation in order to decrease the risk of postoperative formation of a new gliosis. Evaluation of the influence of the human optic media on the iOCT imaging showed satisfactory results with almost no impact of the optic media on visibility of the implant and underlying retina. However, these results are valid only for cases with surgery duration shorter than 3.5 hours and with no corneal swelling. Focal shadowing from the array electrodes onto the retina surface was documented during the study as well, but appeared to be clinically insignificant, as the square of shadowing was minimal. 2. New surgical techniques Pediatric cataract surgery is a complex and difficult. Frequently, the development of PCO or visual axis reopacification can lead to the failure of the surgery. Over 20 years ago, Dr. Tassignon in Belgium developed and introduced a completely novel method of aphakia correction after cataract extraction – the bag-in-the-lens (BIL) IOL implantation technique, which reduced significantly the rate of postoperative VAR (Tassignon et al. 2002). However, the performance of the BIL IOL implantation technique remains challenging and the reasons of the improved outcome after surgery remains debated (Tassignon et al. 2007). In two book chapters, which are the part of this thesis, we summarized our experience of surgical care of pediatric cataract patients, including preparation of the patients, description of surgical complications and preliminary refractive and visual results (Lytvynchuk et al. 2019, Lytvynchuk and Lorenz 2019). Additionally, we performed two studies of use of BIL IOL implantation technique in different age groups of children with cataract. In the first report, we analyzed the postoperative refraction and prediction error in pediatric cataract patients at different age (Lytvynchuk at al. 2019). For the first time, our data demonstrated satisfactory and even slightly better precision of the BIL IOL power calculation in comparison to the data obtained in studies dedicated to conventional lens-in-the-bag or sulcus IOL implantation technique, supporting the efficacy of the new method. The prediction error strongly inversely correlated with age and axial length of the pediatric eyes. In the second study dedicated to BIL IOL technique, we analysed in a large cohort of patients at different age the rate of the most common intra- and early postoperative complications of the BIL IOL technique (Lytvynchuk et al. 2020). The study data demonstrated that the success rate with regard to VAR was 94.4%. There were no significant differences between the age groups concerning intra- or postoperative complications. Another study, which is presented within this thesis, investigates the efficacy of a novel approach – hydraulic centripetal macular displacement – as first option treatment for traumatic macular holes (Ruban, Lytvynchuk et al. 2017). Our data showed that the macular hole closure rate in the group of patients with traumatic MH was 85.7%, which is slightly higher than previously reported. Postoperative TMH closure and improvement of the visual acuity was enabled by intraoperative centripetal displacement of the macula, removal of the chorioretinal scarring and gentle massaging of the macula in centripetal manner. Since the outcome of this new approach is very satisfactory, we suggested this novel technique to be an effective tool in the primary care for traumatic macular hole cases. 3. New surgical instruments Rhegmatogenous retinal detachment remains one of the most frequent emergency situations, and the scleral buckling procedure is the first-choice surgical technique to treat uncomplicated RD. The most important step of this surgical technique is scleral indentation with marking of the retinal breaks onto the sclera. With our new prototype of new scleral depressor-marker we aimed to improve this step of the surgery, making it more precise with less risk for complications and shorter performance time (Lytvynchuk et al. 2019). We demonstrated its effectiveness in regard to separation of two major functions: scleral indentation and scleral marking, in contrast to conventional instrumentation. This could improve the accuracy of marking by placing the mark only onto the desired area. The combination of the light probe with the new instrument improves the precision of the scleral indentation indicating the highest indentation point with the light. Modern development of pharmaceutical agents enables to treat a variety of retinal disorders by injecting them into the vitreous cavity. Intravitreal injection remains to be the most frequently used drug delivery method with relatively low rates of complications. However, since the number of IVIs constantly increases, the number of complications increases as well. Additionally, the reasons for the presence of epiretinal membranes after IVI, postoperative inflammation and retinal detachment remain elusive, making it difficult to further improve the method. The second invention presented here, a new needle for IVI, was aimed to decrease the trauma of the ocular tissues during the injection in order to decrease the risk of potentially injected cellular material, which can play a role in intraocular inflammation (Lytvynchuk et al. 2021). The new needle allowed to reduce the trauma of the ocular tissues and significantly decreased the capture of the cellular content inside the needle tip. Cytological analysis of aspirates taken from the new needle showed almost 50% less cellular content in comparison to a standard hypodermic needle. A custom-made needle prototype demonstrated a higher penetration forces, but the increased values were not statistically significant. Currently, new studies are underway to evaluate the new needle in preclinical and clinical settings. The methods and techniques presented within this habilitation thesis have improved the surgical management of a number of ocular disorders. However, some of these new procedures have just entered clinical stage and remain to be further evaluated. It is therefore necessary and important to continue with the implementation of these techniques and to gather new data on safety and efficacy to ensure optimal outcome of the surgeries.
Klinische Implikationen neuartiger diagnostischer und chirurgischer Methoden in der intraokularen Chirurgie von pädiatrischen und erwachsenen Patienten
Keywords: intraocular surgery; ddc:610